Care of patients with inborn errors of immunity in thirty J Project countries between 2004 and 2021 - Abolhassani, Hassan; Avcin, Tadej; Bahceciler, Nerin; Balashov, Dmitry; Bata, Zsuzsanna; Bataneant, Mihaela; Belevtsev, Mikhail; Bernatowska, Ewa; Bidló, Judit; Blazsó, Péter; Boisson, Bertrand; Bolkov, Mikhail; et al. (Frontiers in Immunology, 2022)
In this study, meeting profiles and major diagnostic and treatment parameters of the J Project (JP) were studied. JP center leaders reported patients’ data from 30 countries representing a total population of 506 567 565. The number of JP meetings increased from 6 per year in 2004 and 2005 to 44 and 63 in 2020 and 2021, respectively. The cumulative number of meetings per country varied from 1 to 59 in various countries reflecting partly but not entirely the population of the respective countries. Altogether, 24,862 patients were reported giving an average prevalence of 4.9. Most of the patients had predominantly antibody deficiency (46.29 %) followed by patients with combined immunodeficiencies (14.3%). The percentages of patients with bone marrow failure and phenocopies of IEI were less than 1 each. The number of patients was remarkably higher that those reported to the ESID Registry in 13 countries. Immunoglobulin (IgG) substitution was provided to 7,572 patients (5,693 intravenously) and 1,468 patients received hematopoietic stem cell therapy (HSCT). Searching for basic diagnostic parameters revealed the availability of both immunochemistry and flow cytometry in 26 countries, and targeted gene sequencing and new generation sequencing was available in 16 countries. The number of IEI centers and experts in the field were 260 and 690, respectively. We found high correlation between the number of IEI centers and patients treated with intravenous IgG (IVIG) (correlation coefficient, cc, 0.994) and with those who were treated with HSCT (cc, 0.868). Similar correlation was found when the number of experts was compared with these two parameters. However, the number of patients treated with subcutaneous Ig only slightly correlated with the number of experts (cc, 0.526) and no correlation was found between the number of centers and patients on SCIG (cc, 0.105).